Step by Step Help for Children with ADHD : a Self-Help Manual for Parents. - Laver-Bradbury, Cathy (Jessica Kingsley Publishers, 2011)
Raising a child with ADHD can be distressing and exhausting for the whole family. But given the appropriate knowledge, and the right tools, parents can intervene to manage their child's behaviour, leading to improved relationships at home and, it is hoped, a more successful time at school. This simple, flexible six-step programme is full of tried-and-tested ideas for parents and professionals supporting families of young children with ADHD. By practicing the techniques and strategies, parents will gain confidence in their parenting and, over time, will improve the child's management of the con.